Analysis of Insurance Services in Financing Insurance at Bank Syariah Indonesia - Tamlija, Tamlija; Imsar, Imsar (UNISSULA, 2025)
This study investigates the implementation of insurance services within financing products at Bank Syariah Indonesia (BSI) Medan Juanda, focusing on service delivery, employee perceptions, and factors influencing its effectiveness. The approach used is qualitative experience-based research, which is carried out through interviews with eight customers and two employees. The findings reveal that the financing insurance services adhere closely to sharia principles, ensuring ethical and transparent processes that align with Islamic financial values. Employees perceive these services positively, acknowledging their significant role in providing customers with added value and financial protection. Supporting factors include a strong internal system and regular employee training, which contribute to effective service implementation. However, challenges such as limited customer understanding and persistent negative perceptions of sharia insurance hinder wider acceptance. The study’s insights emphasize the importance of enhancing customer education and addressing misconceptions to improve trust and satisfaction in Sharia-compliant financing insurance services.